Nilai-nilai Moderasi Beragama dalam Hadis Nabi SAW. - Affandi, Abdullah; Billah, M. Mu'tashim (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2024)
This research discusses religious moderation in Islam through the analysis of the Hadith of Prophet Muhammad SAW, focusing on themes such as tolerance, balance in worship, and the rejection of extremism. Religious moderation, or wasathiyah, emphasizes the importance of balance in beliefs and religious practices, as well as a tolerant attitude towards non-Muslims. The Hadiths indicate that Islam teaches a balance between worship and worldly responsibilities, highlighting the importance of moderate education to shape the character of the younger generation. In the modern context, religious moderation is relevant in addressing the challenges of radicalism and extremism, as well as maintaining harmony in a pluralistic society. This study employs a qualitative approach and thematic analysis to explore the values of moderation in Hadith, with the hope of providing a better understanding of the application of moderation in daily life